Political Reading of Dangarembga’s Nervous Conditions (Language Circle: Journal of Language and Literature, 2020)
This paper explores Tsitsi Dangarembga’s debut novel, Nervous Conditions, from a political perspective. It has been read as portraying of gender relationships, social hierarchies and oppression of African women. This paper takes a different route as it analyses the role of masculinities through a political perspective. The conflict and struggle between genders in the text can be read through a political and historical perspective. This particular reading is permitted through a close analysis of the male characters in the novel. The research argues that male characters resemble or behave in away similar to white colonizers in their treatment of African women. Reading the novel through a political perspective provides the reader with the benefit of understanding the changes that occur in the characters and the role of gender conflict in the text. The triumph of Tambu and Nyasha at the end underscores the failure of colonial power to colonize Zimbabwe.